Response of irrigated wheat cultivars to different nitrogen rates and sources - Marcelo Carvalho Minhoto Teixeira Filho; Salatiér Buzetti; Marcelo Andreotti; Marco Eustáquio de Sá; Orivaldo Arf; Márcio Mohamed Megda (Revista Brasileira de Ciência do Solo, 2009)
High wheat yields require good N fertilization management. The objective of this study was to evaluate the effects of different N applications at sowing using Entec (N source with nitrification inhibitor) and urea (traditional N source) at covering, on four wheat cultivars. The experiment was conducted in a randomized block design in a factorial scheme, with four replications, at the Experimental Station of the Faculdade de Engenharia de Ilha Solteira - UNESP, on a dystrophic, epi-eutrophic alic Red Latosol with loamy texture, formerly under savannah vegetation. Four N rates (0, 60, 120, and 180 kg ha-1) were tested, applied at sowing in the case of Entec and top-dressed 40 days after plant emergence in the case of urea, and the four wheat cultivars E 21, E 22, E 42, and IAC 370. The yield of the wheat cultivars E 21 and E 42 was highest. Plant height and lodging index of cultivar E 22 were greatest, with consequently lowest grain yield. There was no significant difference between Entec (applied at sowing) and urea (top-dressed) in terms of grain yield and yield components. Nevertheless, urea resulted in a higher N leaf content, and Entec in a larger number of undeveloped spikelets. High nitrogen rates influenced the hectoliter mass negatively, affecting wheat grain quality. Grain yield increased under N rates of up to 82 kg ha-1 N, through Entec applied at sowing or top-dressed urea. Altas produtividades de trigo requerem um bom manejo da adubação nitrogenada. O objetivo deste trabalho foi avaliar os efeitos de diferentes doses de nitrogênio na semeadura usando o Entec (fonte de N com inibidor de nitrificação), ou em cobertura, utilizando a ureia, em quatro cultivares de trigo. O experimento foi desenvolvido em área experimental pertencente à Faculdade de Engenharia de Ilha Solteira - UNESP, em um Latossolo Vermelho distrófico epieutrófico álico textura argilosa, o qual foi nativamente ocupado por vegetação de Cerrado. O delineamento estatístico foi o de blocos ao acaso, com quatro doses de N (0, 60, 120 e 180 kg ha-1) na semeadura, usando o Entec, ou em cobertura aos 40 dias (início do alongamento), empregando a ureia e os cultivares E 21, E 22, E 42 e IAC 370, em quatro repetições. Os cultivares de trigo mais produtivos foram o E 21 e o E 42. O cultivar E 22 apresentou maior altura de plantas e altas notas de acamamento, com consequente menor produtividade de grãos. Não houve diferença significativa entre o Entec (aplicado na semeadura) e a ureia (aplicada em cobertura) para produtividade de grãos e para nenhuma das outras avaliações, porém a ureia proporcionou maior teor de N foliar, e o Entec, maior número de espiguetas não desenvolvidas. O incremento das doses de N influenciou negativamente a massa hectolítrica, alterando assim a qualidade dos grãos de trigo. O N aumentou a produtividade de grãos de trigo até a dose de 82 kg ha-1 de N, usando Entec aplicado na semeadura ou ureia aplicada em cobertura.